Food Acquisition Practices, Body Mass Index, and Dietary Outcomes by Level of Rurality. Issue 1 (17th November 2020) - Kegler, Michelle C.; Prakash, Radhika; Hermstad, April; Anderson, Kate; Haardörfer, Regine; Raskind, Ilana G.
Abstract: Purpose: Rural residents are more likely to be obese than urban residents. Research on how people navigate their local food environments through food acquisition behaviors, such as food shopping and restaurant use, in different types of communities may help to create a deeper understanding of the multilevel determinants of obesity. Methods: Data are from a national sample of US adults ages 18‐75. Respondents were recruited from an online survey panel in 2015 and asked about food shopping, restaurant use, diet and weight (N = 3, 883). Comparisons were made by level of rurality as assessed by Rural‐Urban Continuum Codes (RUCC) and self‐reported rurality of the area around their home. Findings: Food acquisition behaviors varied minimally by RUCC‐defined level of rurality, with the exceptions of type and distance to primary food store. Rural residents drove further and were more likely to shop at small grocery stores and supercenters than were residents of semiurban or urban counties. In contrast, all of the food acquisition behaviors varied by self‐reported rurality of residential areas. Respondents living in rural areas shopped for groceries less frequently, drove further, more commonly shopped at small grocery stores and supercenters, and used restaurants less frequently. In multivariable analyses, rural, small town, and suburban areas were each significantly associated with BMI and fruit and vegetable intake, but not percent energy from fat. Conclusion: Findings show that self‐reported rurality of residential area is associated with food acquisition behaviors and may partly explain rural‐urban differences in obesity and diet quality.